A comparative study on two stress intensity factor-based criteria for prediction of mode-I crack propagation in concrete. (June 2016) - Dong, Wei; Wu, Zhimin; Zhou, Xiangming; Wang, Cuijin
Highlights: Initial toughness criterion generally gives better results for concrete of all grades. FPZ length is much longer after PFZ is fully formed based on the nil SIF criterion. The K R -curve obtained from the nil SIF criterion is lower at early fracture stage. Difference from the two criteria becomes larger as concrete strength increases. Different performance due the two cracking criteria on concrete is also elaborated. Abstract: In the analysis of mode-I crack propagation of normal strength concrete at a crack tip, the initial fracture toughness and nil-stress intensity factor (nil-SIF) are two distinguished and widely adopted types of crack propagation criteria. However, there is little information reported on the difference resulting from the two criteria when they are employed to analyze concrete with different strength grades. Aiming at this objective, three-point bending tests are carried out on notched concrete beams of five strength grades, i.e. C20, C40, C60, C80 and C100, and an arrange of initial crack length/depth ratios as 0.2, 0.3 and 0.4, to investigate initial fracture toughness, fracture energy and load–crack mouth opening displacement (P–CMOD) relationship. Meanwhile, the three-point bending tests are also conducted on notched concrete beams of four specimen heights, i.e. 60, 90, 120, and 150 mm. The two aforementioned types of concrete crack propagation criteria are introduced to determine crack propagation and predict the P – CMOD curves of a series of notched concrete beams under a three-point bending test. It has been found that the P – CMOD curves calculated using the initial fracture toughness criterion show a better agreement with experimental results than the ones calculated using the nil SIF criterion. With the increase of concrete strength, the difference between the peak loads from experiment and those from analyses based on the nil-SIF criterion becomes increasingly larger than the scenarios based on the initial fracture toughness criterion. Therefore, it can be reasonably concluded that for the two types of concrete crack propagation criteria, the initial fracture toughness is more appropriate for describing the fracture behavior of concrete, especially for high strength concrete.